The darkness of reacculturation: examining factors influencing depression among Chinese international student returnees in the post-COVID-19 era - Jin, Ruining; Wei, Jie; Wang, Xuanyi; Le, Tam-Tri (Frontiers in Psychology, 2024)
In the aftermath of the COVID-19 pandemic, the reintegration of Chinese international student returnees intersects with China's critical effort to combat a significant brain drain of highly skilled talents, highlighting an unprecedented psychological battleground. This convergence underscores the urgent need for nuanced research to navigate the uncharted territory of their mental health. Employing Bayesian analysis supported by Markov Chain Monte Carlo (MCMC) algorithms, this study examined depression prevalence and associated factors among 1,014 Chinese returnees. The sample comprised 44.87% male participants (455), 51.58% female participants (523), and 3.55% identifying as "Others" (36), with an age distribution of 61.74% aged 18-30 (626), 28.80% aged 31-40 (292), and 9.47% aged 41-50 (96). The mean age of participants was 29.6 years, ranging from 18 to 50 years. PHQ-9 diagnoses revealed alarming levels of depression, with 47.9% exhibiting a moderately severe degree of depressive disorder. Our findings highlight the intricate interplay between identity clusters-"homestayers" (those leaning towards a Chinese cultural identity), "navigators" (those with a bicultural identity), and "wayfarers" (those leaning towards a foreign cultural identity)-and the likelihood of depression. Specifically, homestayers showed a clear and strong negative association, navigators demonstrated a positive association, and wayfarers had a positive yet unclear correlation with depression levels. Furthermore, acculturation, age, and gender showed no significant effects, whereas education mildly mitigated depression. Based on these findings, we suggest the implementation of better-tailored mental health support and policies to facilitate smoother reintegration.